Influence of catalysts used in synthesis of poly(p-dioxanone) on its thermal degradation behaviors. (November 2015) - Li, Xiao-Yang; Zhou, Qian; Wen, Zhi-Bin; Hui, Yan; Yang, Ke-Ke; Wang, Yu-Zhong
Abstract: Thermal degradation behavior and mechanism of aliphatic poly(ether-ester) poly( p -dioxanone) (PPDO) have been intensively explored from the view of chemical structure of polymer. Actually, the trace metal ions derived from synthetic catalyst in the polymer act a non-ignorable role during its thermal degradation. In present work, a series of PPDO were prepared via ring-opening polymerization catalyzed by Novozym 435, SnOct2, ZnEt2 and AlEt3 compounds. Pyrolysis-gas chromatography/mass spectroscopy (Py-GC/MS) was employed to analyze the pyrolysis products of PPDO samples, and thermogravimetry (TG) was used to investigate isothermal and non-isothermal degradation behavior of PPDO under nitrogen as well as air atmosphere. It revealed that the metal residues would accelerate the decomposition of PPDO owing to their catalysis effect, and the activity order was found in Al > Zn > Sn > Novozym 435 in nitrogen atmosphere, otherwise Sn > Al > Zn > Novozym 435 in air atmosphere. Meanwhile, the content of the metal residue was also proved as a key factor to affect the thermal stability of PPDO. Compared a metal-free sample PPDO Sn-0 (Sn content: 0 ppm) with PPDO-Novozym 435, similar decomposition behavior was obtained, which further confirmed that the residual metal from catalyst played a dominant role to deteriorate the thermal stability of PPDO.